Recombined humanized endostatin (Endostar) intravenous infusion in the treatment of refractory nasopharyngeal carcinoma: Three case reports. Issue 32 (August 2019) - Chen, Chen; Liu, Song-Ran; Zhou, Shu; Li, Xiao-Hui; Wang, Xiao-Hui; Tao, Ya-Lan; Chang, Hui; Zhang, Wen-Wen; Li, Wen-Fei; Zhou, Si-Lang; Xia, Yun-Fei
Abstract: Rationale: Refractory nasopharyngeal carcinoma is challenging to treat and at present there is no standard treatment or any good choice. Patient concerns: Although the three patients in our case reports had already underwent multiple treatments before, they still suffered from disease recurrence of nasopharyngeal carcinoma. Diagnosis: They were diagnosed as refractory nasopharyngeal carcinoma. Interventions: A continuous infusion of Endostar, an antiangiogenic agent, combined with chemotherapy and radiation therapy was given to treat the patients. Outcomes: Patients showed complete or partial response to the combined therapy as evidenced by regression of tumors and decrease in plasma Epstein–Barr virus (EBV) DNA load. Lessons: Continuous infusions of Endostar in combination with chemotherapy and/or radiation therapy showed promising efficacy and safety. The combination therapy indicates a new approach to treat refractory nasopharyngeal carcinoma.